A Study on Social Phobia and Functional Disability among Uni-versity Students of Dakshina Kannada District - Akram, MD Shoeeb; Naik, Poonam; Nirgude, Abhay S (National Journal of Community Medicine, 2016)
Introduction: Social phobia is gathering increased attention and recognition as impairing but treatable condition that often starts in adolescence. This study was conducted to study the magnitude of social phobia and functional disability among the first year university students and to study the association of social phobia and functional disability. Method: A cross sectional study was conducted among the first year students of a university situated in Mangalore, Dakshina Kannada district of Karnataka, for a period of one month. Socio-demographic profile of the study participants and information on social phobia and functional disability was collected using a pre-designed and pre-tested questionnaire. Results: Prevalence of social phobia was found to be 41.7%. Female gender, Muslim religion and various faculties were the statistical significant attributes of social phobia (p<0.05). For each disability areas, the difference between the two groups was statistically significant (p<0.001) and SPIN scores was found to have positive correlation with SDS scores (p<0.001). Conclusion: Prevalence of social phobia is high among the university students and requires stringent efforts for early diagnosis and planning appropriate interventions.